Clinical change after the implementation of the Choice and Partnership Approach within an Australian Child and Adolescent Mental Health Service. Issue 1 (20th January 2017) - Naughton, Jonine N.L.; Carroll, Matthew; Basu, Soumya; Maybery, Darryl
Abstract : Background: The Choice and Partnership Approach (CAPA) model has been implemented widely into Child and Adolescent Mental Health Services (CAMHS) in the United Kingdom and similar health systems in Australia and New Zealand. This study investigated whether the implementation of the CAPA model was related to changes in client clinical outcomes and response times within a regional Australian CAMHS. Method: Multiple measures of time, clinical diagnosis, contact and outcomes were collected at intake and discharge for 33 clients prior to and 77 following the implementation of CAPA. Results: A two‐tailed t ‐test showed that the significantly reduced waiting time was associated with the timing of CAPA implementation. The Health of the Nation Outcome Scales for Children and Adolescents information subscale showed a significant post‐CAPA implementation improvement. A chi‐square test for independence showed that the CAPA model group had significantly more initial clinical appointments. Conclusions: After the implementation of CAPA, the flow of young people through the service improved, with children and adolescents being seen in a more timely manner. The findings highlighted that the greater client throughput did not negatively impact upon clinical outcomes. Further prospective research with the completion of multi‐informant outcome measures is recommended.